2009
DOI: 10.1073/pnas.0903438106
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori moves through mucus by reducing mucin viscoelasticity

Abstract: The ulcer-causing gastric pathogen Helicobacter pylori is the only bacterium known to colonize the harsh acidic environment of the human stomach. H. pylori survives in acidic conditions by producing urease, which catalyzes hydrolysis of urea to yield ammonia thus elevating the pH of its environment. However, the manner in which H. pylori is able to swim through the viscoelastic mucus gel that coats the stomach wall remains poorly understood. Previous rheology studies on gastric mucin, the key viscoelastic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
326
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(349 citation statements)
references
References 51 publications
4
326
1
4
Order By: Relevance
“…Estimates for the torque of the enteric motor ranges from ∼1,300 to ∼2,000 pN·nm (20,21). The e-proteobacterium H. pylori has been estimated to swim with torque of 3,600 pN·nm (22), and spirochetes are capable of swimming with 4,000 pN·nm of torque (21,23). Sodium-driven motor torques in Vibrio spp.…”
Section: Significancementioning
confidence: 99%
“…Estimates for the torque of the enteric motor ranges from ∼1,300 to ∼2,000 pN·nm (20,21). The e-proteobacterium H. pylori has been estimated to swim with torque of 3,600 pN·nm (22), and spirochetes are capable of swimming with 4,000 pN·nm of torque (21,23). Sodium-driven motor torques in Vibrio spp.…”
Section: Significancementioning
confidence: 99%
“…While it was necessary to model T. foetus as a prolate ellipsoid, because irregular shapes are too complex, in actuality an undulating membrane wraps around its body from the anterior to posterior region, and it is possible that this structure generates a reduction in drag upon spinning. Further, owing to the motion and position of the flagella and undulating membrane during linear swimming in T. foetus, it is reasonable to hypothesize that the viscoelastic properties of the localized fluid could be altered as a result of interactions occurring at this interface, as reported for other microorganisms [67]. In the work done by Spagnolie et al [65], it was shown that viscoelasticity can either increase or decrease both the swimming speed and/or swimming efficiency of helical bodies depending on geometry, fluid properties and rotation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic expression of LCN-2 mRNA was measured by qRT-PCR and demonstrated a significant increase relative to control mice ( Figure 3E). Faecal LCN-2 is a sensitive and broadly dynamic marker of intestinal inflammation in mice [25]. P-80 fed mice showed elevated fecal LCN-2 levels ( Figure 3F) after four weeks compared to control mice.…”
Section: Effects Of P-80 On Colonic Mucosa and Microbiota Localizatiomentioning
confidence: 99%